Effect of Nutrient Enrichment and Turbidity on Interactions Between Microphytobenthos and a Key Bivalve: Implications for Higher Trophic Levels - Hope, Julie A.; Hewitt, Judi; Pilditch, Conrad A.; Savage, Candida; Thrush, Simon F. (Frontiers in Marine Science, 2020)
Benthic diatoms are a high-quality food resource providing essential fatty acids to benthic grazers. Different stressors may alter the proportion of diatoms and other microalgae and thus can affect the quality as well as quantity of food available to benthic consumers. Microphytobenthos (MPB) lipid biomarkers were assessed in a field experiment to elucidate changes to the biosynthesis of fatty acids (FA) under nitrogen (N) enrichment (three levels) at eight intertidal sites that spanned a turbidity gradient. Influences on the flow of carbon and energy were determined using FA biomarkers of a functionally important deposit-feeding tellinid bivalve (Macomona liliana). Site-specific effects of N enrichment were detected in MPB quantity and quality measurements. Enrichment generally increased MPB biomass (chl a) across all sites, while the proportion of diatom associated fatty acid biomarkers was more variable at some sites. Analysis of sediment FA biomarkers and environmental variables suggested that changes to the microbial community composition and quality were related to water clarity and mud content of the bed. The ability of the MPB to utilize the increased nitrogen, as indicated by the resource use efficiency index, was also important. Despite the increase in MPB biomass, lipid reserves in the tissue of M. liliana, a primary consumer of MPB, were reduced (by up to 6 orders of magnitude) in medium and high N addition plots compared to control plots. Further, the nutritional quality of the bivalves to higher trophic levels (indicated by a lower ratio of essential FAs (ω3:ω6)) was reduced in high treatment plots compared to control plots suggesting the bivalves were adversely affected by nutrient enrichment but not due to a reduction in food availability. This study suggests anthropogenic nutrient enrichment and turbidity may indirectly alter the structure and function of the benthic food web, in terms of carbon flow and ecosystem productivity. This may indirectly change the interactions between MPB and key bivalves as suspended sediment concentrations and nutrient enrichment continue to increase globally. This has implications for various ecosystem functions that are mediated by these interactions, such as nutrient cycling as well as primary and secondary production.